Atrophic vulvovaginitis: new trends in pharmacotherapy - V N Prilepskaya; A V Ledina (IP Berlin A.V., 2013)
The article presents the current data on the etiopathogenesis of atrophic vulvovaginitis, diagnostic criteria, clinical manifestations and modern drugs used to treat the pathological condition.